Speaking Up, Speaking Out : Lived Experiences of Non-Tenure-Track Faculty in Writing Studies - Sanchez, Rachel; McGuire, Meg (Professor); Edwards, Jessica, 1984- (Book collections on Project MUSE., 2021)
"Addresses the experiences of those in the non-tenure-track faculty (NTTF) trenches through storytelling and reflection. By connecting NTTF voices from various aspects of writing studies, offers fresh perspectives and meaningful contributions, imagining the possibilities for contingent faculty to be valued and honored in educational systems that often do the opposite."